Segmental phonology and Black South African English speakers : communicative success with standard dialect listeners - Pascoe, Michelle (Division of Communication Sciences and Disorders, 2017)
The study investigated the nature of the listener confusion which occurs when Black South African English (BSAE) speakers communicate a list of common English words to speakers of standard South African (StdSAE) English. BSAE and StdSAE subjects were grouped into 10 dyads. BSAE subjects read 120 monosyllabic English words to StdSAE subjects. Written data of StdSAE subjects were analysed to determine patterns of success and failure in the communication of single word items by BSAE subjects. Specific difficulties with vowels, dipthongs and consonants are discussed in terms of their effect on intelligibility. Findings are evaluated in the light of previous research, and in terms of Flege's Speech Learning Model (1987, 1991, 1995). It is suggested that all segmental features of BSAE relate to two distinct levels: a functional (meaning) level and an aesthetic level. This study focussed on the functional level, and aimed to describe the segmental features of BSAE speech which affect meaning. Such a distinction has particular relevance for speech and language therapists who need to have a clear rationale for their work with BSAE-speaking clients. Clinical implications specific to this emerging client group within South Africa are discussed.